Pricing Arithmetic Asian Options under Hybrid Stochastic and Local Volatility - Min-Ku Lee; Jeong-Hoon Kim; Kyu-Hwan Jang (Journal of Applied Mathematics)
Recently, hybrid stochastic and local volatility models have become an industry standard for the pricing of derivatives and other problems in finance. In this study, we use a multiscale stochastic volatility model incorporated by the constant elasticity of variance to understand the price structure of continuous arithmetic average Asian options. The multiscale partial differential equation for the option price is approximated by a couple of single scale partial differential equations. In terms of the elasticity parameter governing the leverage effect, a correction to the stochastic volatility model is made for more efficient pricing and hedging of Asian options.